Drug overdose death rates in different countries: Who should be alarmed?. (February 2022) - Snowdon, John
Objectives: This study aims to assess how many nations, in addition to the United States and Canada, report alarmingly high drug overdose death rates, and to compare how those rates have changed. Conclusions: Drug overdose death rates exceed four per 100, 000 in over 10% of the world's nations, including Libya (where rates are increasing) and in Russia (where rates have fallen). A comparison of data from five well-resourced nations with high drug death rates showed recently accelerated and alarming increases in rates in the United States and Canada (attributed to influx of fentanyl, plus increased stimulant use). A reported recent fall in Canada's drug suicide rate may be attributable to misclassification of some suicides as accidents. There is an urgent need to ensure accuracy and better understanding concerning drug overdose deaths and how to prevent them.